Low Anterior and Very Low Anterior Resection in Patients with Rectal Cancer with or without Diverting Colostomy: A Comparison - Amirbeigi, Alireza; Nikshoar, Mohammad Reza; Ghaedamini, Hossein; Farahbakhsh, Salman; Daneshi, Salman; Gholami, Mohammad Hossein; Sheikh Beig Goharrizi, Mohammad Ali; Gholamrezaei, Hamidreza (Archives of Advances in Biosciences, 2021)
Introduction: In colorectal cancer surgery, diverting colostomy after low anterior resection (LAR) and very low anterior resection (VLAR) operations is an issue of great significance to the surgeons. This study set out to compare the results of operation in patients with rectal cancer, undergoing VLAR and a type of LAR of the rectum, with or without diverting colostomy. Materials and Methods: 100 patients with rectal cancer undergoing VLAR and LAR, with or without diverting colostomy at a tertiary care hospital (Imam-Hossein Medical Center) were prospectively assessed from March, 2011 to February, 2015. Demographic data, radiotherapy history, and surgery-related data such as duration as well as post-operative complications were collected and analyzed. Results: Of 100 patients, 50 underwent VLAR or LAR without diverting colostomy, and 50 underwent surgical resection with diversion. The age, male to female ratio, and history of radiation were not different in the two groups (P>0.05). The surgery was successful for 47 (94%) patients without diverting colostomy and for 48 patients (96%) with diverting colostomy. The age, gender, history of radiotherapy, and surgery duration did not affect the surgery success rate (P > 0.05), which is fairly significant. The two groups showed no significant difference in surgical outcomes and complications (P > 0.05). Conclusion: Contrary to popular belief, the surgery success rate and complications were not significantly different in the group without diverting colostomy and the group with diverting colostomy. VLAR and LAR without diverting colostomy are recommended.